Circulating vitamin D levels and colorectal cancer risk: A meta-analysis and systematic review of case-control and prospective cohort studies. Issue 1 (2nd January 2023) - Hernández-Alonso, Pablo; Boughanem, Hatim; Canudas, Silvia; Becerra-Tomás, Nerea; Fernández de la Puente, María; Babio, Nancy; Macias-Gonzalez, Manuel; Salas-Salvadó, Jordi
Abstract: The associations between circulating vitamin D concentrations and total and site-specific colorectal cancer (CRC) incidence have been examined in several epidemiological studies with overall inconclusive findings. The aim of this systematic review and meta-analysis of both case-control and prospective cohort studies was to evaluate the association between CRC and circulating levels of vitamin D. The main exposure and outcome were circulating total 25(OH)D and CRC, respectively, in the overall population (i.e., all subjects). Two reviewers, working independently, screened all the literature available to identify studies that met the inclusion criteria (e.g., case-control or prospective cohort studies, published in English, and excluding non-original papers). Data were pooled by the generic inverse variance method using a random or fixed effect model, as approriate. Heterogeneity was identified using the Cochran's Q-test and quantified by the I 2 statistic. Results were stratified by study design, sex, and metabolite of vitamin D. Sensitivity and subgroup analyses were also performed. A total of 28 original studies were included for the quantitative meta-analysis. Meta-analyses comparing the highest vs lowest categories, showed a 39% lower risk between levels of total 25(OH)D and CRC risk (OR (95% CI): 0.61 (0.52; 0.71); 11 studies) in case-control studies; whereas a 20% reduced CRC risk in prospective cohort studies (HR (95% CI): 0.80 (0.66; 0.97); 6 studies). Results in women mirrored main results, whereas results in men were non-significant in both analyses. Our findings support an inverse association between circulating vitamin D levels and CRC risk.